The Learning Process of Mon Ethnic Identities: A Case Study of Ban Wang Ka, Nong Lu Sub-district, Sangkhla Buri District, Kanchanaburi Province - Chaichana, Nobparat; Jai-aree, Apichart; Tanpichai, Prasong (Trends of Humanities and Social Sciences Research, 2021)
The ethnic Mon of Ban Wang Ka immigrated to Thailand in 1948 mainly because of political reason. Their ethnic identities are results of economic, social and political interactions and selections of cultural differences as their symbols using the past to serve the present. These identities are language, housing, dressing, food, rituals, beliefs, traditions, music and dance. The learning process of Mon ethnic identities happens as community culture where people struggle for wellbeing and survival. Relationship in the community causes production culture. They build a value system with various rituals that lead to a relationship system that makes people in the community live together happily with peace. This illustrates the multi-identities of the ethnic Mon of Ban Wang Ka as reflected in the slogan “Thai bodies with Mon’s hearts”.